Community Participation in the Development of Pottery Tourism Village, Pejagatan Village, Kebumen Regency - Suprapto, Yuni; Putri, Noviani Achmad (Faculty of Social Science, Universitas Negeri Semarang, 2020)
This article tried to discuss the optimization of village potential in the tourism sector. It started with the assumption that changing a village into a tourist village would have a good impact on economic and socio-cultural aspects. This research was conducted in Pejagatan Village, Kutowinangun Sub-district, Kebumen Regency, which is basically a tourism village with the main product of pottery. The discussion emphasized the need for efforts to understand the characteristics and local elements in the village before determining the direction of the policy to be developed. Besides, the participation aspect of the community became the second part in an effort to discuss the optimization of a village's potential. This research was carried out utilizing a qualitative method with case studies as an effort to explore the main data. This method was accompanied by looking at previous studies and related documentation as supporting data.